Effects of diverse property rights on rural neighbourhood public open space (POS) governance: Evidence from Sabah, Malaysia - Gabriel Hoh Teck Ling; Pau Chung Leng; Ho Chin Siong (Economies, 2019)
There are severe issues of public open space (POS) underinvestment and overexploitation. However, few studies have been conducted on the property rights structure and its impacts on rural commons governance, specifically concerning local neighbourhood residential POS quality and sustainability. The social-ecological system framework and the new institutional economics theory were employed to examine the local diverse property rights system and its effects on the emergence of POS dilemmas. Rural commons covering neighbourhood residential Country Lease (CL) and Native Title (NT) POS from the districts of Kota Kinabalu and Penampang, Sabah Malaysia were selected. A mixed-method phenomenological case study, involving multi-stakeholders' perspectives across public-private-user sectors, was employed. This study revealed four main interconnected property rights issues, including attenuated rights, incomplete rights, maladaptive rights, and security-based de facto perceptive rights, under the complex state-private regime, which incentivise the opportunistic behaviour of individuals in externalising POS commons dilemmas. The findings further inferred that the local diverse property rights issues and POS dilemmas caused, and are associated with, other rights issues and dilemmas, forming a rights-dilemmas nexus. Not only do the institutional failures actuate POS dilemmas, but the former also engender other forms of property rights failures, while the latter cause other POS dilemmas. This paper suggests policy and management insights to public officials, in which the importance of the institutional-social-POS behavioural factor and the re-engineering of POS governance via adaptive property rights realignment are emphasised.
Keywords: D01; D02; D23; D62; K11; O21; P25; Q24; Q26; 330; diverse property rights effects; property rights failures; transaction costs; commons dilemmas; rural; neighbourhood; Residential Public Open Space (POS); resource governance and management; Sabah Malaysia